Blended Learning: Study of a formative assessment in the flipped classroom model - Souza, Juliana (Archives of Business Research, 2020)
Summative and formative assessments are important for students' learning pathway. The article analyzes the blended learning model in the Entrepreneurship discipline, in two classes from the perspective of a learning experience as formative assessment, applied in the online platform. The study pointed out that students' access to content increases when participation is stimulated through a formative activity in the online environment. In the class of 54 students, 37 students performed the activity, while in the other class of 76 students, 67 students performed the activity in the online environment.